Hubungan Usia Ibu Hamil Dengan Preeklmasia Di Poli Kandungan - Noradilla, Ema; Andayani, Sestu (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Introduction: Maternal mortality rate (MMR) is a complex health problem that is influenced by various factors, one of which is preeclampsia. Risk factors for preeclampsia include maternal age, gravida, obesity, and other comorbidities. This study aims to analyze the relationship between the age of pregnant women and the incidence of preeclampsia in the Gynecology Clinic of Jombang Hospital. Methods: This study used a correlational analytic design with a retrospective approach. The population in this study was medical record data of pregnant women on June 01-August 30, 2024 at Jombang District Hospital with gestational age > 20 weeks who visited in the period June 1-August 30, 2024 at Jombang District Hospital (N=494). Samples were taken by random sampling as many as 221 respondents. The independent variable was maternal age, while the dependent variable was the incidence of preeclampsia. Data analysis using Chi-square test. Results: Most of the pregnant women (53.39%) were at the age of 20-35 years (n=118). The statistical test results showed a value of ρ=0.313 (ρ>0.05), which indicated no significant relationship between maternal age and the incidence of preeclampsia. Conclusion: There is no significant relationship between the age of pregnant women and preeclampsia in the Gynecology Clinic of Jombang Hospital. Other factors such as obesity, gravida, and comorbidities may be more influential. It is recommended that pregnant women regularly check their pregnancy for early detection of preeclampsia risk. Keywords: Age, Pregnant Women, Preeclampsi